MENUMBUHKAN KREATIVITAS DENGAN MODEL PEMBELAJARAN: TINJAUAN PUSTAKA - Siti Muntamah, Bening; Fardana N, Nur Ainy (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
This research aims to discuss learning models that can help teachers foster students' creativity. Creativity is one of the skills that a person needs in his life, and creativity can develop because it is not something static, so it is important to provide the right stimulus. This research uses a literature study. The literature used is in the form of publications collected from the Web of Science and Scopus databases in the period 2014–2023. The keywords used were